MICROSTRUCTURE OF ULTRA-HIGH PERFORMANCE CEMENTITIOUS COMPOSITES WITH AND WITHOUT EXCESSIVE SULFATES - NAHHAB, ALI H.; GESOĞLU, MEHMET; GÜNEYISI, ERHAN; YAZICI, HALIT (Journal of Duhok University, 2017)
Advances in the science of cement-based materials have resulted in the development of a new generation of material, namely ultra-high performance cementitious composite (UHPCC). The primary improvements of UHPCC are achieved by the removal of coarse aggregate, limiting the water-to-binder ratio and introducing micro fine materials such as silica fume. The present study aimed to investigate the microstructure of UHPCC with and without additional sulfates. For this purpose, two groups of UHPCC were designed at a constant water/binder  ratio of 0.174.The first group of UHPCC mixtures was designed with binary blends of Portland cement and silica fume and was reinforced with 2% micro steel fibers by volume. The other group was also designed with binary cementitious blends but without fibers. Each group consisted of five mixes with different SO3 contents of between 0.11% and 4.5% by weight of natural sand. For each mix, the UHPCC samples were either standard cured or steam cured at 80 ˚C over a 48 h. Besides, UHPCs were compared to Portland cement mortars. The microstructures of the UHPC were examined using scanning electron microscopy (SEM). Energy dispersive X-ray analysis (EDX) was also performed. SEM observations showed the existence of non-expansive ettringite in the UHPCC samples containing excessive sulfates.